Pengaruh Iklim Organisasi Terhadap Motivasi Kerja Karyawan Dinas Perindustrian dan Perdagangan Provinsi Sumatera Utara - Dimas Rahmat Depri (Al-Istimrar: Jurnal Ekonomi Syariah, 2022)
This study aims to determine the effect of organizational climate on work motivation of employees of the Department of Industry and Trade of North Sumatra Province. The type of research used in this study is quantitative research and data collection techniques in this study using questionnaires that were informed to respondents. The data analysis methods used in this research are data quality test, classical assumption test, simple linear regression test, hypothesis testing and determination R2 testing. Results Based on the research shows organizational climate (X) has a positive and significant influence on work motivation (Y). The results of the t-test (partial) obtained a value of sig 0.00 <0.05, because the provisions of the t-test (partial) can be said that Ho is partially accepted and partially organizational climate (X) affects work motivation (Y).